Bullwhip Effect Phenomenon and Mitigation in Logistic Firm's Supply Chain: Adaptive Approach by Transobrder Agency, Canada - Riffat Faizan; Adnan Ul Haque (International Journal of Supply Chain Management, 2015)
Abstract: Purpose: This case study explores the bullwhip effect phenomenon and mitigation in supply chain process at Transborder Logistic Canada. Problem statement: Despite being one of the largest logistic chains of Canada, Transborder for two years was facing challenges and problem in shape of bullwhip effects. To add further to the firm's problem there is no owned-warehouse to manage its inventories. Theoretical Framework: The theoretical framework for present case study is based on the theory of Lee (1977) to overcome the problems in the supply chain process. Moreover, the steps of Hussain and Drake (2011) are considered to overcome the bullwhip effects, challenges of cost control, response time, risk management, and effective warehouse management. Methodology: "Realism" is the research philosophy undertaken to develop a cross-sectional research design to investigate the research problem at hand. Hypothetico-inductive-deductive model is used to explore research variables. Moreover, researcher used mixed method approach by circulating matrix based semi-structured survey questionnaire in different interlinked departments of Transborder Agency. The questionnaire is based on LIKERT Scale (1-to5) rating. In addition to that, open-ended interviews with the head and subordinates of various departments were commenced to explore qualitative aspects related to research problem. Findings and Implications: results revealed that logistic firm rely heavily on demand-forecasting information through customers. There was fluctuation in demand order along with order batching, demand forecast updating, rationing and shortage game, and price fluctuation. The Polar diamond approach is considered by Transborder to effectively and efficiently deal with problem at hand and challenges that are hindering the supply chain process. Moreover, VMI, EDI, and POS are tools and techniques used to resolve different types of challenges and find a long term proper rational solution to bullwhip effect (problem at hand). Moreover, findings revealed that However, there is still need for effective warehouse management which can be done through developing strategic alliance with various partners across the globe and undertaking the software inventory system to manage things in correct manner. Research Value: The present research contributes to dynamic field of supply chain through providing new insight dimension of bullwhip effect in logistic business and enhancing the body of knowledge. The results could facilitate logistic supply chain's parties to avoid similar type of problems so that competitiveness is enhanced. Moreover, it contributes towards empirical research as there is very limited work available on Canada's logistic industry. Conclusion: Logistic supply chain inefficiency is mainly caused by bullwhip effect. The rational adoption of model can assist supply chain managers to be proactive in approach. Moreover, the rational decision can help in identification of problem at early stage and help the firm to efficiently overcome the problem.